Roles of LncRNAs in Viral Infections - Liu, Weiwei; Ding, Chan (Frontiers in Cellular and Infection Microbiology, 2017)
Many proteins and signaling pathways participate in anti-viral host responses. Long non-coding RNAs (lncRNAs), a subset of non-coding RNAs greater than 200 nucleotides in length, have been recently described as critical regulators in viral infections. Accumulating research indicates that lncRNAs are important in the development and progression of infectious diseases. LncRNAs are not only involved in anti-viral responses, but in many different virus-host interactions, some of which may be beneficial to the virus. Here we review the current knowledge regarding host and viral lncRNAs and their roles in viral infections. In addition, the potential of using lncRNAs as diagnostic biomarkers is discussed.